Studi Pemahaman Masyarakat Dusun Pasir Malang tentang Hadis Etika Memilih Pemimpin - Akhsa Alpar Mubarok; Muhammad Faqih Choiruddin; Muhammad Alif (Program Studi Ilmu Hadis STAIN Mandailing Natal, 2024)
This study examines the understanding of the people of Dusun Pasir Malang regarding the ethics of selecting a leader from the perspective of Hadith. The ethics of choosing a leader is crucial because it significantly impacts the sustainability of community life. However, in reality, many people still choose leaders based on personal or group interests without considering the ethical values taught by Islam. This research uses a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation study. The findings show that the people of Dusun Pasir Malang have a low level of awareness regarding the application of Hadith in selecting leaders. The understanding of Hadith concerning leader criteria, such as trustworthiness, honesty, and responsibility, has not yet been optimally implemented. This study is expected to serve as a reference to raise public awareness about the importance of selecting leaders based on Islamic ethical values.